Influence of Steatite and Fly Ash on the Fresh-Hardened Properties and Micromorphology of Self-Compacting Concrete - S. Christopher Gnanaraj; Ramesh Babu Chokkalingam; G. Lizia Thankam; S. K. M. Pothinathan (Advances in Materials Science and Engineering)
This experimental study investigates the effect of steatite and fly ash on the fresh and hardened properties of self-compacting concrete (SCC). Accordingly, ordinary Portland cement (53 grade) was replaced with various fractions of fly ash (10% and 20%) and with various percentages (5%, 10%, 15%, 20%, and 25%) of steatite by weight of cement as a filling material. European guidelines for self-compacting concrete guidelines were adopted for producing SCC. The fresh concrete properties were studied using the slump flow test, T500 test, L-box test, and V-funnel test, whereas the hardened properties of SCC were studied by the cube compression test, splitting tensile strength test, and flexural strength test on various days (7 days, 14 days, 28 days, and 90 days). In addition to that, microstructural studies were carried out to justify the hardened concrete results. The result shows that the steatite content reduces the flow properties of concrete, whereas the fly ash content increases the flow properties. In terms of strength, addition of fly ash enhanced the later age strength, whereas up to 15% of replacement with steatite improved the compressive, tensile, and flexural strength, beyond which there is a fall in the strength parameters which is however higher than the control specimen.